2017
DOI: 10.1097/bcr.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ocular Burn Injuries Requiring Surgery

Abstract: The surgical management of severe ocular burns is challenging and often associated with variable long-term outcome. The aims of this study were to analyze the clinical course of these injuries and determine the factors associated with the need for surgery. A retrospective medical records review was conducted for patients admitted to the Victorian Adult Burns Services, with ocular burns, from January 2000 to January 2010. One hundred and twenty-nine patients were admitted with ocular burns, of which 17 (13.2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Following title/abstract review, 7924 articles were excluded and 534 articles were eligible for full-text review. Following full-text review, 8 articles were eligible and included in the systematic review (Table 1) [2, 1521]. All 8 articles were eligible for final data extraction and meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following title/abstract review, 7924 articles were excluded and 534 articles were eligible for full-text review. Following full-text review, 8 articles were eligible and included in the systematic review (Table 1) [2, 1521]. All 8 articles were eligible for final data extraction and meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These 272 surgical cases were compared to 535 non-surgical cases. The most reported anatomical structure was the eye (7/8 studies) [2, 1621], surgical intervention was AMT (5/8 studies) [16, 17, 1921], outcome was visual acuity on initial evaluation and at follow-up (5/8 studies) [1620], and complication was corneal vascularization at follow-up (6/8 studies) [1621]. The eyebrow was reported in 0/8 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an Australian study reported by Cabalag et al, from a total of 3340 burns admissions, around 35% suffered facial burns with 12% involving the orbital/ periorbital region [ 11 ]. In another study on a large number of patients (4758 patients: 2346 adults and 2412 children) from United Kingdom, 18% of the burns involved the face and 2% were periorbital burns requiring surgical treatment [ 4 ].…”
Section: Discussionmentioning
confidence: 99%